The effect of acupressure on muscle cramps in patients undergoing hemodialysis - Kolsoom Mohmadi; Nahid Shahgholian; Mahboubeh Valiani; Hossein Mardanparvar (Wolters Kluwer Medknow Publications, 2016)
Background: Pain resulting from muscle cramps is one of the most common outcomes of hemodialysis. One of the mechanisms associated with muscle cramps is unnatural muscle metabolism. Because acupressure improves muscle metabolism through the releasing of energy, this study was performed with the purpose of determining the impact of acupressure on muscle cramps. Materials and Methods: This study was a single-blind clinical trial. Accordingly, 64 patients were selected and intensity and frequency of muscle cramps were determined by randomly categorizing them into two groups. The intervention group received 9 sessions of acupressure and the control group received 9 sessions of placebo intervention. The intervention was performed 15 min before hemodialysis in both groups. In both the groups, average intensity of pain and the frequency pain was compared before, after, and 1 month after completion of the intervention. Results: Data analysis revealed that there were no significant statistical differences between the two groups in terms of mean value of intensity (P = 0.586) and frequency (P = 0.780) of muscle cramps before the intervention. We observed a significant difference after completion of intervention sessions (P < 0.001). Moreover, there were no significant differences between mean value of intensity (P < 0.001) and frequency (P = 0.030) of muscle cramps in the control group before, after, and 1 month after the completion of 9 sessions of placebo intervention. Conclusions: Employing acupressure may result in decrease of muscle cramps in patients undergoing hemodialysis.